Cranioplasty After Severe Traumatic Brain Injury: Effects of Trauma and Patient Recovery on Cranioplasty Outcome - Posti, Jussi P.; Yli-Olli, Matias; Heiskanen, Lauri; Aitasalo, Kalle M. J.; Rinne, Jaakko; Vuorinen, Ville; Serlo, Willy; Tenovuo, Olli; Vallittu, Pekka K.; Piitulainen, Jaakko M. (Frontiers in Neurology, 2018)
Background: In patients with severe traumatic brain injury (sTBI) treated with decompressive craniectomy (DC), factors affecting the success of later cranioplasty are poorly known. Objective: We sough to investigate if injury- and treatment-related factors, and state of recovery could predict the risk of major complications in cranioplasty requiring implant removal, and how these complications affect the outcome. Methods: A retrospective cohort of 40 patients with DC following sTBI and subsequent cranioplasty was studied. Non-injury related factors were compared with a reference population of 115 patients with DC due to other conditions. Results: Outcome assessed one day before cranioplasty did not predict major complications leading to implant removal. Successful cranioplasty was associated with better outcome, whereas a major complication attenuates patient recovery: in patients with favorable outcome assessed one year after cranioplasty, major complication rate was 7%, while in patients with unfavorable outcome the rate was 42% (p=0.003). Of patients with traumatic subarachnoid hemorrhage (tSAH) on admission imaging 30% developed a major complication, while none of patients without tSAH had a major complication (p=0.014). Other imaging findings, age, admission Glasgow coma scale, extracranial injuries, length of stay at ICU, cranioplasty materials, and timing of cranioplasty were not associated with major complications. Conclusion: A successful cranioplasty after sTBI and DC predicts favorable outcome one year after cranioplasty, while stage of recovery before cranioplasty does not predict cranioplasty success or failure. tSAH on admission imaging is a major risk factor for a major complication leading to implant removal.